356 Examining Use and Beliefs about Sleep Medications in a Sample of Older Adults: The Role of Hypnotic Dependency. (3rd May 2021) - Tully, Isabelle; Simpson, Norah; Dietch, Jessica; Tutek, Joshua; Manber, Rachel
Abstract: Introduction: Prevalence of insomnia and prescription of sleep medications increases in older adults and is associated with heightened risk of falls, cognitive and psychomotor detriments, and exacerbation of pre-existing conditions. The present study aimed to characterize beliefs about sleep and sleep medications, hypnotic self-efficacy, and hypnotic dependence in a sample of older adults with insomnia disorder. Methods: Adults 50 years and older (N = 141) who met DSM-5 criteria for insomnia disorder were enrolled in the RCT of the Effectiveness of Stepped-Care Sleep Therapy In General Practice (RESTING) study. At baseline, participants completed the Beliefs about Medications Questionnaire (BMQ; subscales assess the belief that hypnotics are necessary and concern regarding consequences of use), Insomnia Severity Index (ISI), Dysfunctional Beliefs and Attitudes about Sleep Scale (DBAS), Pre-Sleep Arousal Scale (PSAS), and the Patient Health Questionnaire-4 (PHQ-4). Participants taking prescription sleep medications (n = 54) also reported if they had sedative hypnotic reduction goals and completed the Sleep Medications Dependency Scale and Hypnotic Self-Efficacy Scale. Results: Those taking prescription sleep medications reported greater belief in the necessity of sedative hypnotics (p < .001, d = 1.69) and greater anxiety and depression (p = .005, d = .57) than those not taking prescription medications; groups did not differ significantly on the BMQ concern subscale, ISI, DBAS, or PSAS. 70.4% of participants using prescription sleep medications endorsed decrease in sedative hypnotic use as a treatment goal. Dependency on sleep medications, but not hypnotic self-efficacy, was greater in those with this goal (p = .003, d = .94). Higher levels of hypnotic dependence were associated with both greater concern (r = .40, p = .003) and belief in the necessity of sleep medications (r = .48, p < .001). Conclusion: Our findings indicate that many treatment-seeking older adults with insomnia disorder take prescription sleep medications. They tend to believe in the necessity of sleep medications for controlling sleep disruption, but also identify medication reduction as a treatment goal, even if endorsing dependence on hypnotics. This highlights the importance of disseminating non-medication treatments that address both insomnia and reduction of sedative hypnotic use. Support (if any): 1R01AG057500